2019
DOI: 10.1007/s00453-019-00649-7
|View full text |Cite
|
Sign up to set email alerts
|

The Parameterised Complexity of Computing the Maximum Modularity of a Graph

Abstract: The maximum modularity of a graph is a parameter widely used to describe the level of clustering or community structure in a network. Determining the maximum modularity of a graph is known to be NP-complete in general, and in practice a range of heuristics are used to construct partitions of the vertex-set which give lower bounds on the maximum modularity but without any guarantee on how close these bounds are to the true maximum. In this paper we investigate the parameterised complexity of determining the max… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The general problem of correlation clustering (Bansal et al, 2004) and the subproblem of maximizing modularity (Brandes et al, 2007;Meeks and Skerman, 2020) are known to be NPcomplete. However, modularity maximization is known to be Fixed-Parameter Tractable (FPT) when parametrized by the size of the minimum vertex cover of the graph (Meeks and Skerman, Frontiers in Complex Systems frontiersin.org 2020).…”
Section: Exact Optimizationmentioning
confidence: 99%
“…The general problem of correlation clustering (Bansal et al, 2004) and the subproblem of maximizing modularity (Brandes et al, 2007;Meeks and Skerman, 2020) are known to be NPcomplete. However, modularity maximization is known to be Fixed-Parameter Tractable (FPT) when parametrized by the size of the minimum vertex cover of the graph (Meeks and Skerman, Frontiers in Complex Systems frontiersin.org 2020).…”
Section: Exact Optimizationmentioning
confidence: 99%
“…Furthermore it is NP-hard to approximate modularity to within any constant multiplicative factor [12]. Modularity maximisation is also W [1]-hard, a measure of hardness in parameterised complexity, when parameterised by pathwidth; but approximating modularity to within multiplicative error 1 ± ε is fixed parameter tractable when parameterised by treewidth [35]. The reduction in [6] required some properties of optimal partitions; for example it was shown that a vertex of degree 1 will be placed in the same part as its neighbour in every optimal partition.…”
Section: Properties Of Modularitymentioning
confidence: 99%